Formes et fonctions de la « donnée » dans trois webs environnementaux sud-américains (Argentine, Bolivie, Brésil) - Pierre Gautreau; Marta Severo; Timothée Giraud; Matthieu Noucher (Netcom)
This paper analyzes simultaneously different levels of organization of three environmental webs from South America (Argentina, Brazil, Bolivia), revealing general trends in the forms of mobilization of downloadable data by environmental actors of these countries. The research highlights the reduced role of “data” in the structuring of these South American environmental webs: nor the differentiation of communication strategies, nor the level of websites’ authority is clearly explained by the nature of downloadable data. This happens regardless of the country. Beyond this point, this research confirms the heuristic interest for analyzing the importance given to “data” in websites, as a method to identify emerging communication practices by environmental actors. More particularly, it provides a better understanding of the kind of constraints that the State faces with the digital transition in environmental matters, questioning its centrality in the production and circulation of environmental information. In this context, the State has to face a rising competition from other non-public actors. In order to maintain its centrality in the circulation of information, its strategies range from the indexing of public and private data to digital “soft power” actions through dissemination of reference datasets.